Immunohistochemical characteristic of expression levels of Kі-67, p16INK4a, HPV16 in cervical intraepithelial neoplasia and cervical cancer - V. A. Tumanskiy; Z. A. Pyrogova (Zaporozhye State Medical University, 2017)
Squamous cervical cancer (SCC) is a common tumor in women, which is preceded by the series of pathological processes, among which the key role is played by cervical intraepithelial neoplasia (CIN). Aim. To study the characteristics of immunohistochemical (IHC) expression of Ki-67, p16INK4a, HPV16 in squamous cervical epithelium (SCE) with dysplastic changes of varying degree (CIN I-III) and also in the tumor cells of SCC. Materials and methods. Pathohistological and IHC studies of uterine cervix biopsies from 53 patients (the age ranged from 18 to 45 years) were performed. Results. It was found that SCE with CIN I is characterized by the low Ki-67 expression level (Me = 17.87 % (13.76, 22.44)) and the extremely low p16INK4a expression level (Me = 0.00 CUOD (0.00; 29.64)). The proportion of HPV16-positive patients with CIN I is 27.27 %. CIN II is characterized by the average proliferation level in SCE (Me = 44.96 % (34.91, 55.41)) and the moderate p16INK4a expression level (Me = 75.71 CUOD (51.24, 82, 41)). The proportion of HPV16-positive patients with CIN II is 71.43 %. CIN III is characterized by the high proliferation level (Me = 74.62 % (68.50, 84.67)) and by the high p16INK4a expression level of in SCE (Me = 117.47 CUOD (95.38, 123, 93)); the proportion of HPV16-positive patients with CIN III is 77.78%. In all the patients with SСС, nuclear and cytoplasmic expression of HPV16 was detected in the tumor cells. High expression levels of Ki-67 and p16INK4a were detected in the tumor cells. There are direct correlations between the expression levels of Ki-67, p16INK4a, HPV16 and CIN degree. Conclusions. These data indicate that the expression levels of Ki-67, p16INK4a and HPV16 increase with the increasing of CIN grade. The absence of statistically significant differences between the expression levels of Ki-67, p16INK4a and HPV16 in CIN III and the same levels in the tumor cells of SCC indicates that these markers cannot be used for differential diagnosis between CIN III and SCC.